Continuous iteration of dynamical maps - Aldrovandi, R. [UNESP]; Freitas, L. P. [UNESP] (AIP Publishing, 1998)
A precise meaning is given to the notion of continuous iteration of a mapping. Usual discrete iterations are extended into a dynamical flow which is a homotopy of them all. The continuous iterate reveals that a dynamic map is formed by independent component modes evolving without interference with each other. An application to turbulent flow suggests that the velocity field assumes nonseparable values. © 1998 American Institute of Physics.